METODE RESITASI BERMEDIA DRESSING FRAME SET TERHADAP KEMAMPUAN BINA DIRI PADA ANAK AUTIS DI SLB - Mardika Wulansari, Wisma (Jurnal Pendidikan Khusus, 2016)
ABSTRACT The research about recitation method with dressing frame set media toward self-guide ability to autism children in SLB Harmoni was formed background by the ability of autism children in self-guide using latching school uniform which needed to be developed so the researcher gave interesting and fun activity through recitation method with dressing frame set media. The recitation method with dressing frame set media was not applied yet before in SLB Harmoni Sidoarjo. The purpose of this research was to prove whether there was influence in learning self-guide wearing and latching school uniform using recitation method with dressing frame set in SLB Harmoni Sidoarjo. The method of this research used quantitative approach and the data was collected by using initial observation, final observation, and documentation. The initial and final observations were used to obtain the data of wearing and latching school uniform ability to autism children before and after giving treatment while the documentation was used as the support data or a proof that the research was really done. The research result indicated that before research the average obtained was 47,2 and after research the average obtained was 70,6. In addition, the value of Tcounting = 0 was smaller than Ttable = 2 with significant level 5%. If Tcounting < Ttable it could be concluded that there was influence of recitation method with dressing frame set media toward self-guide ability to autism children in SLB Harmoni Sidoarjo.     Keywords: Recitation, dressing frame set, self-guide